Menakar Peran Kepuasan Dalam Penciptaan Loyalitas Tamu Restoran Di Kawasan Kota Lama Semarang - Kurniawati, Emaya; Santoso, Aprih (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
The aim of the research is to empirically test the quality of service, trust and loyalty towards restaurant guest satisfaction in the Old City area of Semarang. The research method used in this research is a quantitative method. Based on calculations using the Slovin formula, the research sample was 100 respondents. The research results show that service quality and trust have a positive and significant influence on restaurant guest loyalty in the Kota Lama area of Semarang. Loyalty also has a positive and significant effect on restaurant guest satisfaction in the area. Satisfaction mediates the influence of service quality on restaurant guest loyalty, as well as mediates the influence of trust on restaurant guest loyalty in the Kota Lama area of Semarang.